Respuesta:
Hola!
Explicación paso a paso:
-((-6) + (-2) - (-16) + (-4) - (-7))=
-( - 6 - 2 + 16 - 4 + 7 ) =
- ( 11) =
-11
-[(-6) + (-2) + 16 + (-4) +7 )]
-[ (- 12) + 23]
-( 11 )
= - 11
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
Respuesta:
Hola!
Explicación paso a paso:
-((-6) + (-2) - (-16) + (-4) - (-7))=
-( - 6 - 2 + 16 - 4 + 7 ) =
- ( 11) =
-11
Respuesta:
-[(-6) + (-2) + 16 + (-4) +7 )]
-[ (- 12) + 23]
-( 11 )
= - 11